Does peer acceptance promote active academic engagement in early adolescence? A robust investigation based on three independent studies. (March 2023) - Lan, Xiaoyu
Abstract: Does peer acceptance promote active academic engagement in early adolescence? The existing theoretical and empirical evidence seemingly supports this commonly assumed positive relationship, but extant research has sometimes shown that peer acceptance can create risks that potentially decrease youth proactive academic engagement. The present research critically examined this divergent finding across three independent but interrelated studies, postulating mediating by grit (i.e., perseverance and passion for long-term goals). Early adolescents aged 10 to 13 drawn from different regions in China participated in this multi-informant study. Generally, the results were replicated, indicating that multi-informant assessment of peer acceptance was positively related to grit; in turn, grit was positively associated with academic engagement. This partially indirect role of grit was, however, highlighted only when peer acceptance was assessed by self-report and not when peer acceptance was evaluated by peer-nominated procedure. The current findings not only provide a robust, theoretically driven evaluation of the relationship between peer acceptance and academic engagement, but also offer insights into the underlying mechanism of this relationship through grit in early adolescence. Based on these findings, I discuss the theoretical implications and data-supported school-based intervention initiatives. Highlights: This study examined the relationship between peer acceptance and academic engagement. Converging evidence supported this commonly assumed positive relationship. Grit fully or partially mediated this positive relationship. The full or partial mediation model hinged on varied informants of peer acceptance.